Charging effects on the critical temperature of the Josephson-coupled layered superconductors - Nakhmedov, EP; Cakroglu, O; Huner, M; Al-Shibani, K (ELSEVIER, 1998)
Effects of quantum phase fluctuations on the critical temperature T-c of Josephson-coupled layered superconductors are considered. T-c is shown to decrease nonlinearly with increasing charge fluctuations. The results obtained for the critical temperature by applying the self-consistent mean field method reveal no phase transition from superconducting state to normal metal for a finite value of charging energy. The destruction of the long range phase coherence appeared to occur at asymptotically large values of self-capacitance charging. For the weak quantum phase fluctuations limit, T-c is obtained to be vary in the interval of T-c* J(perpendicular to) = kT(c)((2)) where J(perpendicular to) approximate to kT(c)((2)) is the value of J(perpendicular to) when the superconductor normal metal phase transition takes place. However, the condition J(perpendicular to) greater than or equal to kT(c)((2)) contradicts to the existence of the Josephson coupling between superconducting layers. (C) 1998 Elsevier Science B.V.
Keywords: HIGH-TC SUPERCONDUCTORS; GRANULAR SUPERCONDUCTORS; PHASE-TRANSITION; MAGNETIC-FIELD; QUANTUM FLUCTUATIONS; JUNCTION ARRAYS; COLLECTIVE MODE; ONSET; Physics